International study on nurses' views and experiences of compassion. (September 2016) - Papadopoulos, I.; Zorba, A.; Koulouglioti, C.; Ali, S.; Aagard, M.; Akman, O.; Alpers, L.‐M.; Apostolara, P.; Biles, J.; Martín‐García, Á.; González‐Gil, T.; Kouta, C.; et al.
Abstract : Background: Compassion is considered the cornerstone of nursing practice. However, the recent failures in delivering high‐quality compassionate nursing care in the UK's National Health Service have brought the topic of compassion to the attention of the public, service providers, policy makers and academics. Aim: The aim of this study was to explore the nurses' views and experiences of a number of compassion‐related issues in nursing and describe similarities and differences at an international level as well as from the different nursing roles of the participating nurses. Methods: An exploratory, cross‐sectional descriptive study, using the International Online Compassion Questionnaire. A total of 1323 nurses from 15 countries completed the questionnaire. Results: The majority of participants (59.5%) defined compassion as "Deep awareness of the suffering of others and wish to alleviate it" but definitions of compassion varied by country. Of participants, 69.6% thought compassion was very important in nursing and more than half (59.6%) of them argued that compassion could be taught. However, only 26.8% reported that the correct amount and level of teaching is provided. The majority of the participants (82.6%) stated that their patients prefer knowledgeable nurses with good interpersonal skills. Only 4.3% noted that they are receiving compassion from their managers. A significant relationship was found between nurses' experiences of compassion and their views about teaching of compassion. Conclusion: Our study is unique in identifying the views and experiences of nurses from 15 different countries worldwide. The findings reveal that compassion is neither addressed adequately in nursing education nor supported in the practice environment by managers. Limitations: Self‐report bias was inherent to our survey study design. Furthermore, the individual cultural differences and similarities in the findings are difficult to extrapolate owing to the fact that our analysis was at country level, as well as at the level of the participating nurses. Implications for nursing policy: Understanding the influence of culture on nurses' views about compassion is critical in the current multicultural healthcare environment and merits further research. This will potentially drive changes in nursing education (ensuring that compassion is taught to nurses) and in the way healthcare leaders and managers foster a compassionate culture within their organizations (e.g. by leading by example and compassionate to their staff).